Immunohistochemical determination of calbindin-D28k in the kidney of postnatal rats - Timurkaan, S; Tarakci, BG (Czech Academy Agricultural Sciences, 2004)
The localization of calbindin-D28k was examined in rat kidney at different stages of development. Calbindin was found specifically in the distal convoluted tubules (DCT). In the 10 day old rat kidney many cells apparently belonging to the collecting tubules were positive. In the neonatal nephrons there was also localization of calbindin-D28k to the limb of Henle, suggesting a difference in the regulation of intracellular calcium during maturation. Proximal tubule, renal corpuscle and macula densa gave no specific localization of calbindin-D28k.
Keywords: immunohistochemistry; calbindin-D28k; kidney; rat